(3bhGYO GdRQcTis - (3eMeO Hf HgGOQ Hf YHO Gddg GdRQcTj, CHh YHO Gddg, HOQ GdOjf,J (B794 (3g` s ((3eMeO Hf eMeO GdShOGfi GdMfai s)
(3ChdgG (B:s
(3CeG HYO aEf VHW GdCehQ GdefJTQI GdeJYOOI ai GdbhGfjf GdeJMOI s
(3BNQgG (B:s
(3hcGf CSJGPg aNQGdOjf GdQGRi jMaX YTQI BdGa fcJI ai GdLOd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI NGeSI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B121s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs